Mickey Rooney & Judy Garland collection. Babes in arms [videorecording (DVD)] - Berkeley, Busby, 1895-1976; Rooney, Mickey; Garland, Judy; Winninger, Charles, 1884-1969; Rodgers, Richard, 1902-1979; Rodgers, Richard, 1902-1979 (Turner Entertainment Co. : Distributed by Warner Home Video, 2007)
Learning that his parents are in financial straits, the son of a famous vaudeville team rounds up all the stage kids and puts on a lavish show to raise money. The future looks rosy until a hurricane washes the whole enterprise away on opening night.